2001
DOI: 10.1002/sia.1098
|View full text |Cite
|
Sign up to set email alerts
|

Composition and structure of enriched alloy layers in filmed Al alloys studied by medium‐energy ion scattering

Abstract: The topmost 20 nm of an electropolished Al-1 at.% Cu alloy has been investigated at sub-nanometre resolution using medium-energy ion scattering. Differences in the composition and depth of the enriched Cu layer are observed. Most significantly, the enriched layer contains regions of differing structure and/or lattice orientation with Cu atoms located in distinct ordered regions, consistent with the presence of Cu-rich clusters. Surface-segregated Si and Cu are observed and Cl and Cu are found in the oxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The detailed distribution of copper atoms within the enriched alloy layer may also play a role; evidence from MEIS suggests that copper atoms may form clusters. 23 The potential may also be increased by an enhanced rate of oxygen reduction, due to either thinning of the oxide, allowing increased electron tunneling, or increased influences of flaws, if these contribute significantly to the cathodic current. However, MEIS results for the present alloys indicate a relatively constant thickness of the residual oxides.…”
Section: Discussionmentioning
confidence: 99%
“…The detailed distribution of copper atoms within the enriched alloy layer may also play a role; evidence from MEIS suggests that copper atoms may form clusters. 23 The potential may also be increased by an enhanced rate of oxygen reduction, due to either thinning of the oxide, allowing increased electron tunneling, or increased influences of flaws, if these contribute significantly to the cathodic current. However, MEIS results for the present alloys indicate a relatively constant thickness of the residual oxides.…”
Section: Discussionmentioning
confidence: 99%
“…Habazaki et al 37 observed tungsten-rich oxide fingers, projecting from the film/alloy interface, above the tungsten-enriched layer, during anodizing of a tungsten-containing aluminum alloy. Bailey et al 38 investigated the outer 20 nm of an electropolished Al-1 atom % Cu alloy, using medium-energy ion scattering, suggesting discrete clusters of copper-rich material in the copper-enriched layer. Similarly, it is believed that copper-rich precursor clusters are formed in the copper-enriched layer during anodizing of the AA 2099-T8 aluminum alloy.…”
Section: Nmmentioning
confidence: 99%
“…22 Briefly, a 100 keV He C ion beam of lateral dimensions 1.0 mm ð 0.5 mm was incident on the specimen at an angle of 45°from normal and scattered He C ions were detected by a toroidal electrostatic analyser at a scattering angle of 90°. The twodimensional raw data (scattered ion energy and angle) were subsequently integrated over an angular range of š0.35°at 90°to produce an energy spectrum.…”
Section: Medium-energy Ion Scatteringmentioning
confidence: 99%